Sistem Pendidikan dan Pendidikan Sejarah di Singapura Sebagai Refleksi bagi Pengembangan Kurikulum di Indonesia - Djunaidi Bunglai (Jurnal Pendidikan Sejarah, 2015)
This paper examines the history of the education system and education in Singapore to reflect forcurriculum development in Indonesia. The results show, that the education system in Singaporeand Indonesia are relatively not much difference. The differences even in consistency and consequentof both countries in implementing it. The Ministry of Education of Singapore is very consistent andconsequently, the opposite occurs in Indonesia.The consistency of government and the consequences ofit has been a factor of excellence in the education system of Singapore. The next finding , development ofeducational curriculum in high school history in Singapore prepared with a very broad scope , holistic andphilosophical orientation, global competition based on perennialism, humanism , and reconstrucionism,so that they can participate to realize the advantages of education in Singapore.